MANAJEMEN KEPALA MADRASAH DALAM MENINGKATKAN MUTU TENAGA PENDIDIK DI MADRASAH ALIYAH SWASTA INSAN KESUMA MADANI NAMORAMBE KABUPATEN DELI SERDANG - Retno Pringadi; Amiruddin Siahaan; Makmur Syukri (Research and Development Journal of Education, 2023)
This research is to describe how the Management of Madrasah Heads in Improving the Quality of Educators in Private Madrasah Aliyah Insan Kesuma Madani Namorambe Deli Serdang Regency is one way to develop the quality of teaching staff to improve the quality of educational institutions. Madrasah heads and teachers are free to take disinitiative and be creative in carry out the projected programs to achieve the set targets. Principal leadership is a way or effort to influence, encourage, guide, direct and mobilize teachers, staff, students and parents as well as other parties related to the madrasah to work together/play an active role in achieving the goals that have been set together. The type of research used is a type of qualitative research with a naturalistic approach. Collection of research evidensi obtained by observation techniques, interviews and documentation studies. The evidensi analysis step is to collect data, reduce evidensi and then conclude the data. To test the validity of the data, credibility, transferability, dependability and confirmability were carried out. The findings of this study reveal three related findings regarding: 1) The strategy used by the madrasa head is to use the Normal-Reeducative Strategy approach, namely the process of innovation and training for parties with direct or indirect interest according to a certain time unit. 2) The madrasa head facilitates and encourages teachers in madrasas to be more productive, proactive in utilizing existing resources. 3) Readiness for pedagogic competence, readiness for personal competence, readiness for social competence, readiness for professional competence.